2016
DOI: 10.17221/151/2015-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Breeding triploid plants: a review

Abstract: Wang X., Cheng Z.-M., Zhi S., Xu F. (2016): Breeding triploid plants: a review. Czech J. Genet. Plant Breed., 52: 41-54.Triploid plants have larger organs, greater biomass, and strong stress resistance by preserving relatively larger amounts of photosynthetic energy. The undesirable spread of non-native invasive crop and horticultural plants into natural areas can also be reduced or eliminated by the use of triploids, because they tend to be sterile and seedless. Triploid plants have great economic value and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 98 publications
0
59
0
Order By: Relevance
“…The ability of isolated endosperm tissue to proliferate and regenerate has been proved for a wide range of species (Hoshino et al 2011;Wang et al 2016;Winarto et al 2018) including the genus Actinidia, like A. deliciosa (Goralski et al 2005) or A. kolomikta (Asakura and Hoshino 2017). The experimental system that had previously been established for obtaining the endosperm-derived callus in A. deliciosa (Goralski et al 2005) was also found to be appropriate for A. arguta (not published).…”
Section: General Ultrastructure and Histology Of A Callus With A Divementioning
confidence: 99%
“…The ability of isolated endosperm tissue to proliferate and regenerate has been proved for a wide range of species (Hoshino et al 2011;Wang et al 2016;Winarto et al 2018) including the genus Actinidia, like A. deliciosa (Goralski et al 2005) or A. kolomikta (Asakura and Hoshino 2017). The experimental system that had previously been established for obtaining the endosperm-derived callus in A. deliciosa (Goralski et al 2005) was also found to be appropriate for A. arguta (not published).…”
Section: General Ultrastructure and Histology Of A Callus With A Divementioning
confidence: 99%
“…However, this statement refers primarily to pollen, for which a mean fertility of 31.9% is reported in triploid angiosperms. Reliable figures for female gametes are scarce (Bicknell and Koltunow 2004 ; Parisod and Besnard 2007 ; Sharbel et al 2009 ; Schinkel et al 2016 ; Wang et al 2016 ) and need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Plants with triploid chromosomes have morphological characteristics of large organs, large biomass and resistance to environmental stress conditions, as well as an increase in photosynthetic energy (Wang et al, 2016;Shanko, 2017).…”
Section: Resultsmentioning
confidence: 99%